Strategi Pengembangan Usaha Kain Sasirangan dengan Pemanfaatan Platform Digital saat Pandemi Covid-19 di Kota Banjarmasin - Muhammad Shodiq Permana; Dessy Maulina (PPJP Universitas Lambung Mangkurat, 2023)
This Study aims to analyze the Sasirangan MSMEs Business development strategy in Banjarmasin City by utilizing digital platforms during the Covid-19 pandemic. The research method used is descriptive qualitative in the form of responses from sources and participants through interviews and questionnaires. The data analysis method used is the SWOT analysis technique. The result of this Study indicates that the condition of the survival of the Sasirangan MSMEs during the Covid-19 pandemic caused a drastic decrease in sales levels. However, market growth slowly began to increase from early 2020 to 2021. Next, the use of digital platforms by Sasirangan SMEs in Banjarmasin City is still not optimal, so a re-analysis is needed to apply digital-based sales. Based on calculations through the IFAS and IFAS matrices, it shows that the Sasirangan MSMEs are in quadrant I, so an SO strategy can be applied that can take advantage of the strength of the business to get the available opportunities by adding product variations with adjustment to consumer tastes and expanding the marketing network by digital-based media.